2017
DOI: 10.1016/j.seppur.2017.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Direct immobilization of laccase on titania nanoparticles from crude enzyme extracts of P. ostreatus culture for micro-pollutant degradation

Abstract: Direct immobilization of laccase on titania nanoparticles from crude enzyme Direct immobilization of laccase on titania nanoparticles from crude enzyme extracts of P. ostreatus culture for micro-pollutant degradation extracts of P. ostreatus culture for micro-pollutant degradation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…Immobilized laccase from Cerrena unicolor C-139 eliminated 80% of BPA, 40% of NP, and 60% of triclosan from solutions that contained 50 μmol of each endocrine disruptor, respectively (Songulashvili, Jimenez-tobon, Jaspers, & Penninckx, 2012). Also, Debaste, Songulashvili, and Penninckx (2014) was recorded with carbamazepine after 48 hr (Ji, Nguyen, Hou, Hai, & Chen, 2017). The poor elimination of carbamazepine in the study was attributed to the high redox potential of the compound, which hampered its oxidation by the enzyme (Hata, Shintate, Kawai, Okamura, & Nishida, 2010;Ji et al, 2017).…”
Section: P Otential Of Le S In the Eliminati On Of Ed C In Wa S Te mentioning
confidence: 87%
See 4 more Smart Citations
“…Immobilized laccase from Cerrena unicolor C-139 eliminated 80% of BPA, 40% of NP, and 60% of triclosan from solutions that contained 50 μmol of each endocrine disruptor, respectively (Songulashvili, Jimenez-tobon, Jaspers, & Penninckx, 2012). Also, Debaste, Songulashvili, and Penninckx (2014) was recorded with carbamazepine after 48 hr (Ji, Nguyen, Hou, Hai, & Chen, 2017). The poor elimination of carbamazepine in the study was attributed to the high redox potential of the compound, which hampered its oxidation by the enzyme (Hata, Shintate, Kawai, Okamura, & Nishida, 2010;Ji et al, 2017).…”
Section: P Otential Of Le S In the Eliminati On Of Ed C In Wa S Te mentioning
confidence: 87%
“…The authors, therefore, concluded that oxidative products of BPA had a redox mediator effect on the degradation of carbamazepine. The findings from the study suggested that the "presence of more reactive micropollutant can promote the removal of the more recalcitrant pollutants" in a cocktail (Ji et al, 2017).…”
Section: P Otential Of Le S In the Eliminati On Of Ed C In Wa S Te mentioning
confidence: 96%
See 3 more Smart Citations